2018
DOI: 10.3389/fimmu.2018.00931
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hematopoietic Cell Development and Function Through Phosphoinositides

Abstract: One of the most paramount receptor-induced signal transduction mechanisms in hematopoietic cells is production of the lipid second messenger phosphatidylinositol(3,4,5)trisphosphate (PIP3) by class I phosphoinositide 3 kinases (PI3K). Defective PIP3 signaling impairs almost every aspect of hematopoiesis, including T cell development and function. Limiting PIP3 signaling is particularly important, because excessive PIP3 function in lymphocytes can transform them and cause blood cancers. Here, we review the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 190 publications
(488 reference statements)
0
21
0
Order By: Relevance
“…SHIP-1 is a negative regulator of cell signaling in a variety of hematopoietic cells through phosphoinositide; and it dephosphorylates PIP3 to PI-3,4-bisphosphate, effectively reducing or terminating the downstream signaling of the PI3K pathway. 33 SHIP-1 participates in the process of several lung diseases such as asthma, lung injury, and chronic obstructive pulmonary disease. 5,34,35 Evidence showed that SHIP-1 KO mice develop a series of pathologies characterized by progressive non-resolving lung inflammation, fibrosis, and emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…SHIP-1 is a negative regulator of cell signaling in a variety of hematopoietic cells through phosphoinositide; and it dephosphorylates PIP3 to PI-3,4-bisphosphate, effectively reducing or terminating the downstream signaling of the PI3K pathway. 33 SHIP-1 participates in the process of several lung diseases such as asthma, lung injury, and chronic obstructive pulmonary disease. 5,34,35 Evidence showed that SHIP-1 KO mice develop a series of pathologies characterized by progressive non-resolving lung inflammation, fibrosis, and emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Upon resolution of the stress, PI3K inactivation is required for the re-entry of HSCs into quiescence. Thus, PI3K activity in HSCs needs to be tuned into an appropriate window [ 5 , 79 ].…”
Section: Regulation Of Hsc Fate and Malignancymentioning
confidence: 99%
“…Thus, PI3K is considered to be a promising target for therapy and PI3K inhibitors are mainly used for chemotherapeutic agents for hematological malignancies [ 76 ]. The PI3Kδ inhibitor, Idelalisib, has been approved for treating relapsed chronic lymphocytic leukemia (CLL), follicular B-cell non-Hodgkin lymphoma, and small lymphocytic Lymphoma [ 78 , 79 ]. Other PI3K inhibitors including S14161, the p110α-selective inhibitor AS702630, the p110β-selective inhibitor TGX-115, and the p110δ inhibitors IC87114 and CAL-10180 have been developed and regulate the proliferation and survival of leukemic blasts [ 76 ].…”
Section: Regulation Of Hsc Fate and Malignancymentioning
confidence: 99%
“…PI3K activates and produces second messenger PIP3, which activates AKT through phosphorylation of AKT protein at Ser308 [23]. GSK-3β is a downstream target of phosphorylated AKT, which promotes the degradation of Snail, while phosphorylation of GSK-3β leads to its inactivation.…”
Section: Discussionmentioning
confidence: 99%